Beginning Android programming : develop and design - Grant, Kevin (PeachPit, 2014)
In this straightforward guide, Android programming experts Chris Haseman and Kevin Grant show you how to use the powerful set of Android tools to begin writing the next generation of Android applications. After a tour of how to install and configure the Android Studio and Eclipse, you jump right in, building your first Android project. The pair demonstrate how to use the major building blocks for creating an intuitive and good-looking interface. Next, they shows you how to retrieve data and use lists to display data. Chris and Kevin then explore how to use services--important, and often under-utilized, components of the Android platform. The two examine how to handle media and location services before showing you how to write applications for the diverse Android ecosystem and--finally--publish your application.